Estimasi Produksi Padi Menggunakan Data Citra Satelit Landsat 8 dan Sistem Informasi Geografis di Kabupaten Sambas Kalimantan Barat - Masara'T, Sudirman; Santoso, Pande Putu Agus (Universitas Lampung, 2024)
Food security is a challenge in almost all developing countries with low to middle-income levels, including Indonesia. Rice, as one of the primary food sources and a pillar of Indonesian society, has shown a decline in both production and productivity in recent years. This decline in rice production and productivity is attributed to the conversion of productive rice fields due to the high input costs required for each planting season. This situation arises from the limited ability of farmers to make accurate production estimates over large areas and within short timeframes. This research was conducted in Sambas Regency, West Kalimantan, in 2024 with the goal of estimating rice production using satellite imagery technology and geographic information systems (GIS) in Sambas Regency. The data used were obtained through sampling methods in each sub-district, and the imagery data were acquired from Landsat 8 satellites, processed using the Normalized Difference Vegetation Index (NDVI) combined with GIS, and analyzed using QGIS 3.36.3 software. The analysis indicates that the coefficient of determination for rice productivity is highly influenced by the NDVI value, which is 90%, with the formula y = 3.9453x + 0.5287. Consequently, the average rice production in Sambas Regency in 2024 is 2.36 tons/ha.Keywords : imagery, NDVI, Qgis, rice